PASAMBAHAN MANJAPUIK MARAPULAI PADA UPACARA PERKAWINAN DI KENAGARIAN KOTO-TINGGI KECAMATAN BASO KABUPATEN AGAM: Analisis Semiotik - Meria Putriani; Abdurahman Abdurahman; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2012)
The purpose of this study is to find the meaning contained in the text Pasambahan Manjapuik Marapulai in Kenagarian Koto-Tinggi Sub-district Baso Regency Agam Districtusing semiotic theory. This study uses semiotic theory proposed by Charle Sanders Pierce. This research looks at the signs contained in text form Pasambahan Manjapuik Marapulai symbol, index and icon. Data collected through library research, observation, interviews and some of the data taken from the internet. Data analysis was done descriptively. The results of these findings are the first, there are 31signs symbols, 5 marks icon and 3marks index. The results of this study are the signs contained in the text Pasambahan Manjapuik Marapulai. Next, look for the inner meaning behind these signs. The meaning contained in the  only explicit but implied meaning of meaning and cultural semiotic meanings.